2006
DOI: 10.1063/1.2346258
|View full text |Cite
|
Sign up to set email alerts
|

Growth, structure, and properties of epitaxial thin films of first-principles predicted multiferroic Bi2FeCrO6

Abstract: We report the structural and physical properties of epitaxial Bi 2 FeCrO 6 thin films on epitaxial SrRuO 3 grown on (100)-oriented SrTiO 3 substrates by pulsed laser ablation.The 300 nm thick films exhibit both ferroelectricity and magnetism at room temperature with a maximum dielectric polarization of 2.8 µC/cm 2 at E max = 82 kV/cm and a saturated magnetization of 20 emu/cc (corresponding to ~ 0.26 µ B per rhombohedral unit cell), with coercive fields below 100 Oe. Our results confirm the predictions made us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 12 publications
(13 reference statements)
7
90
1
Order By: Relevance
“…The value of saturated magnetization is typical for antiferromagnets with weak ferromagnetism induced by a canted spin structure and the value of RT spontaneous magnetization corresponds well to the previously published results. 4,5,10 The low value (∼ 0.3 µ B /f.u.) of magnetization at saturation of the film regarding the expected theoretical value of 2 µ B /f.u.…”
Section: 2021mentioning
confidence: 99%
“…The value of saturated magnetization is typical for antiferromagnets with weak ferromagnetism induced by a canted spin structure and the value of RT spontaneous magnetization corresponds well to the previously published results. 4,5,10 The low value (∼ 0.3 µ B /f.u.) of magnetization at saturation of the film regarding the expected theoretical value of 2 µ B /f.u.…”
Section: 2021mentioning
confidence: 99%
“…The saturation magnetizations observed in these ceramics are about one order of magnitude higher than disordered perovskite compounds 3,15 and are even two times as high as single crystalline Bi͑Fe 1/2 Cr 1/2 ͒O 3 epitaxial thin films. 7 We believe that the observed magnetic behavior is dictated by the B-site cation order in the ceramics. As mentioned previously, the solid solution can be expressed as a double perovskite compound Pb͓Sc 2x/3 Fe ͑1/2−2x/3͒ ͔ ϫ͓Fe 1/6 W 1/3 ͔O 3 when it is fully ordered.…”
mentioning
confidence: 99%
“…Recent experimental work confirmed that the Bi͑Fe 1/2 Cr 1/2 ͒O 3 epitaxial thin film is isostructural to BiFeO 3 with a rhombohedral distortion. 7 A saturation magnetization of only 0.26 B / f.u. was measured at room temperature due to the absence of long range cation order.…”
mentioning
confidence: 99%
“…The popular room-temperature multiferroic BiFeO 3 (for a more complete discussion see Chapter 3) circumvents this contradictory B-cation 3d-filling requirements [17] with ferroelectricity and magnetism originating from different A and B cations respectively. This has motivated the search for related compounds such as Bi 2 CrFeO 6 wich was predicted to be multiferroic with a large polarization from first principles [18], and later demonstrated experimentally on thin films [19,20]. We will see here that d 0 -ness is in fact not always mandatory and that various strategies can be developed to allow ferroelectricity and magnetism to coexist in ABO 3 compounds.…”
Section: Introductionmentioning
confidence: 99%